2021
DOI: 10.1038/s41598-021-94118-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and consequences of casein kinase II and ankyrin-3 regulation of the epithelial Na+ channel

Abstract: Activity of the Epithelial Na+ Channel (ENaC) in the distal nephron fine-tunes renal sodium excretion. Appropriate sodium excretion is a key factor in the regulation of blood pressure. Consequently, abnormalities in ENaC function can cause hypertension. Casein Kinase II (CKII) phosphorylates ENaC. The CKII phosphorylation site in ENaC resides within a canonical “anchor” ankyrin binding motif. CKII-dependent phosphorylation of ENaC is necessary and sufficient to increase channel activity and is thought to influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Total internal reflection fluorescence (TIRF) microscopy followed standard procedures ( Staruschenko et al, 2005 ; Abd El-Aziz et al, 2021 ). In brief, fluorescence emissions from membrane eYFP-tagged ENaC were collected in COS-7 cells at room temperature using TIRF microscopy to selectively illuminate the plasma membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Total internal reflection fluorescence (TIRF) microscopy followed standard procedures ( Staruschenko et al, 2005 ; Abd El-Aziz et al, 2021 ). In brief, fluorescence emissions from membrane eYFP-tagged ENaC were collected in COS-7 cells at room temperature using TIRF microscopy to selectively illuminate the plasma membrane.…”
Section: Methodsmentioning
confidence: 99%
“…El-Aziz and coworkers now proposed that casein kinase II-phosphorylated bENaC promotes Ank-3-mediated trafficking to the membrane. Principal cell-specific Ank-3 knockout mice showed decreased ENaC activity and increased sodium excretion supporting evidence that Ank-3 binding increased channel activity [52]. The ankyrin repeat domain 36 (ANKRD36) mediates a variety of protein-protein interactions and was found to be significantly lower expressed in hypertension [53 && ].…”
Section: Selected Recent Regulators Of Epithelial Sodium Channel Func...mentioning
confidence: 98%
“…The subcellular localization of ENaC on the apical side of epithelial cells determines either competition for the furin site by the SARS-CoV-2 spike protein in the Golgi apparatus or the failure of cleaved one to be smoothly transported to the apical side, which results in the functional loss of ENaC in pulmonary fluid regulation. It has been demonstrated that by interfering with casein kinase II (CK II) signaling or knocking down CK II phosphorylation and ankyrin-3 binding sites, the translocation and activity of ENaC are reduced, proving that CK II is essential for the function of ENaC and proper localization to the apical side [ 42 , 43 , 44 ]. A recent quantitative mass spectrometry-based phosphorylation proteomics study showed that two subunits of CK II, CSNK2B, and CSNK2A2, interacted with SARS-CoV-2 N proteins to drive changes by affecting the subcellular localization of CK II or sterically blocking the entry of kinases, which may interfere with the phosphorylation of β-ENaC and its subcellular localization ( Figure 1 II) [ 45 ].…”
Section: Relationship Of Sars-cov-2 Infection and Lung Impairmentmentioning
confidence: 99%